Challenges to Accessing Pediatric Health Care in the Mississippi Delta - Roy Grant MA; Andres Ramgoolam MD, FAAP; Ryan Betz BA; Laura Ruttner MPH; John J. Green PhD (SAGE Publishing, 2010)
Background: Increases in hospital emergency department use have been driven by insured patients with problems accessing primary care services. Access problems are especially pronounced in rural communities with health professional shortages. This qualitative study explored reasons for nonurgent pediatric emergency department use in the Mississippi Delta. Method: Using a community-based participatory research framework, a semistructured survey was administered face-to-face in a hospital emergency department waiting room with parents/caregivers who brought their children. Interviews were done over 144 hours in 2-hour blocks covering regular "business hours" and "after hours" (evenings/weekends). Open-ended items allowed qualitative data to be gathered describing reasons for emergency department use and perceptions of urgency of the visit in the parents'/caregivers' own words. Results: There were 112 children, with a response rate of 87%. The mean child age was 5.7 years; 52% were male; 95% were African American and 5% white; 80.6% had Medicaid/SCHIP, 7.8% commercial, and 3.9% other insurance; 7.8% were uninsured. Most (88%) had a usual source of pediatric care. Only 24.3% tried to obtain care before emergency department visit; 23.2% said their children required "urgent" care. Mean distance from home to usual source of care was 10 miles. Ten percent cited transportation as a barrier to keeping health care appointments; 5.5% cited insurance or cost. Families who used the emergency department during evening/weekends were significantly more likely to have cited clinic hours of operation as a reason care was not sought previously than were "business hours" users, who emphasized convenience. Conclusion: Nonurgent pediatric emergency department use could be reduced by extending clinic hours, adding a walk-in service, and making transportation more available.